Association between vascular access type with profile hemodialysis patient in west Nusa Tenggara district hospital - Nurul Hasanah Makmur; Maz Isa Ansyori; I Gede Yasa Asmara; I Gusti Ngurah Ommy Agustriadi (Journal of Indonesia Vascular Access, 2022)
Intoduction: Currently, the prevalence of chronic kidney disease (CKD) is an increasing public health problem. In Indonesia, CKD increased from 0.2% in 2013 to 0.38% in the year 2018. CKD requires very high maintenance and handling costs for hemodialysis. To be able to do hemodialysis, it is necessary to create vascular access as a pathway for blood circulation from the patient's body to the hemodialysis machine. This research is to determine the profile of vascular access and the association between vascular access with comorbid, age, and sex. Methods: This research is descriptive quantitative research, cross sectional. Data were taken from the registration data or medical record of CKD patient that undergo hemodialysis at West Nusa Tenggara Distric Hospital. Data collection was carried out from 10th January 2020 to 10th March 2020. By applying certain inclusion and exclusion criteria, there were 100 obtained data and subsequently were analyzed using SPSS software. Univariate and bivariate analysis using chi-square test were carried out to descrive the data distribution and the association between variables respectively. Result: Of the 100 respondents, it was found that most of them were female 57%. Most data were aged 48-58 years 43% people. The most comorbid is Diabetes Mellitus with 53% of people. The most used vascular access is AV Fistula Brachiocephalic 58.0%. Based on the Chi-Square statistical test, it shows that there is a significant association between vascular access with the comorbid disease (p <0.05) p = 0.003, and the present association between vascular access to sex was obtained p-value = 0.001 (p <0.05) and there is no significant association between the use of vascular access to age showed a value (p> 0.05) p = 0.08. Based on this study to determine vascular access, comorbid and sex are considered in decision making. Conclusion: The research shows that there is association between the vascular access type to comorbidities and gender.